2020
DOI: 10.24127/ajpm.v9i4.3044
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Metakognitif Siswa Dalam Menyelesaikan Permasalahan Pada Materi Pola Bilangan Ditinjau Dari Brain Dominance

Abstract: Penelitian ini bertujuan untuk menganalisis kemampuan metakognitif siswa SMP dalam menyelesaikan permasalahan pada materi pola bilangan ditinjau dari brain dominance. Penentuan subjek berdasarkan brain dominance siswa kelas VIIIC SMP Negeri 13 Madiun. Berdasarkan angket brain dominance yang dibagikan diperoleh 4 subjek yang terdiri dari 2 subjek left brain dominance dan 2 subjek right brain dominance. Jenis penelitian yang digunakan adalah penelitian kualitatif. Teknik pengumpulan data dalam penelitian ini ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…At the elementary school level, there are student misunderstandings [8] Critical thinking skills Student errors occur on different questions [3] Deswita reported that division is more difficult to learn than addition, subtraction, multiplication because in thinking of division there is a guessing step [3]. Thus, to help students who do not understand the estimation step because they do not know the division (mentally) in calculating porogapet using the inverse division approach from multiplication, they have strong reasons [4].…”
Section: The Right Teaching Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…At the elementary school level, there are student misunderstandings [8] Critical thinking skills Student errors occur on different questions [3] Deswita reported that division is more difficult to learn than addition, subtraction, multiplication because in thinking of division there is a guessing step [3]. Thus, to help students who do not understand the estimation step because they do not know the division (mentally) in calculating porogapet using the inverse division approach from multiplication, they have strong reasons [4].…”
Section: The Right Teaching Strategymentioning
confidence: 99%
“…Lusiana et al reported the profile of creative thinking of students with high logicalmathematical intelligence in solving mathematical problems. The creativity studied is the creativity stage that appears at every stage of problem-solving, so that the creativity profile of students with high logical-mathematical intelligence in solving linear equation system problems is presented at each problem-solving step [8]. They uses contextual-based linear equations while researchers use division approach the opposite of multiplication to work on porogapet questions, but both have similarities, namely in the scope of arithmetic material so that researchers assume by providing adequate knowledge of arithmetic division students can be creative in problem-solving for porogapet questions and other arithmetic problems in the form of division instead.…”
Section: The Right Teaching Strategymentioning
confidence: 99%
“…The second category is research on the role of student metacognition. The study concluded that the role of student metacognition is to build a well-composed mathematical frame of mind (Anggo et al, 2014), helping strategies to improve students' cognitive abilities (Nugrahaningsih, 2012), building students' thinking skills to solve a problem (Lusiana et al, 2020). Metacognition also plays a role in controlling and building students' cognition so that thinking becomes more effective and efficient (Sholihah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Students aged 6-12 years still need closeness to home and parents because the home and family are the most comfortable and safe shelters (Allen, 2010;Damayanti & Margaretha, 2021;Winarsih, 2021). When the care and education of children at a young age is entrusted to caregivers at the boarding school who are not the biological parents of these children, it can affect their ability to use aspects of metacognition (Almasitoh & Nugrahaningsih, 2021;Lusiana et al, 2020;Setyaningsih et al, 2020), motivation, and behavior in participating in their learning process.…”
Section: A Introductionmentioning
confidence: 99%